2012
DOI: 10.1074/jbc.m111.320580
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ras Guanine Nucleotide Releasing Protein 4 in FcϵRI-mediated Signaling, Mast Cell Function, and T Cell Development

Abstract: Background: RasGRP4 is one member of the RasGRP family and is highly expressed in mast cells. Results: Fc⑀RI signaling, mast cell function, and thymocyte development are severely impaired by RasGRP1 and RasGRP4 deficiency. Conclusion: This study indicated that the RasGRP family is important in mast cells and T cells.Significance: This work demonstrates immune cells employ multiple members of the RasGRP family to activate the Ras-Erk pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…The lack of a difference between RasGRP1 KO and RasGRP1/3 DKO mice contrasts the finding of the Zhang group where RasGRP4-defient mice showed no impairment in β-selection, but the combined loss of RasGRP1 and 4 showed a more profound phenotype than RasGRP1 deficiency alone. This suggests that RasGRP4 could compensate somewhat for the loss of RasGRP1 [24]. The difference observed between RasGRP1/3 DKO and RasGRP1/4 DKO is likely due to relatively higher expression of RasGRP4 than RasGRP3 in DN3 thymocytes as reported by the Immunological Genome Project [24], [34].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The lack of a difference between RasGRP1 KO and RasGRP1/3 DKO mice contrasts the finding of the Zhang group where RasGRP4-defient mice showed no impairment in β-selection, but the combined loss of RasGRP1 and 4 showed a more profound phenotype than RasGRP1 deficiency alone. This suggests that RasGRP4 could compensate somewhat for the loss of RasGRP1 [24]. The difference observed between RasGRP1/3 DKO and RasGRP1/4 DKO is likely due to relatively higher expression of RasGRP4 than RasGRP3 in DN3 thymocytes as reported by the Immunological Genome Project [24], [34].…”
Section: Discussionmentioning
confidence: 68%
“…Recent reports published by Zhu et al and Kortum et al showed that RasGRP1- and RasGRP1/4- deficient mice showed impaired development beyond DN3, suggesting impaired β-selection [24], [25]. However, the involvement of RasGRP family members in the hallmark events of β-selection was not explored in detail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RasGRP family consists of four RasGEFs, RasGRP1-4. Work from our laboratory and others has shown that RasGRP1-deficient mice exhibit impaired transition through the b-selection checkpoint (28,29). Furthermore, RasGRP1-deficient mice show a dramatic defect in thymocyte-positive selection and invariant NK T cell development (30)(31)(32).…”
mentioning
confidence: 99%
“…Furthermore, RasGRP1-deficient mice show a dramatic defect in thymocyte-positive selection and invariant NK T cell development (30)(31)(32). Aside from RasGRP1, only RasGRP4 has been shown to contribute to T cell development, specifically during the b-selection checkpoint (29). Roles for RasGRP2 or RasGRP3 have not been thoroughly examined in the context of T lymphopoiesis.…”
mentioning
confidence: 99%